Quantifying the Survival Benefit for Allogeneic Stem Cell Transplantation in Relapsed Acute Myeloid Leukemia - Armistead, Paul M. (2009)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the recommended therapy for patients with relapsed AML despite little evidence showing a survival benefit for patients who undergo HSCT vs. chemotherapy alone. Because a prospective randomized trial addressing this issue is unlikely to be conducted we retrospectively reviewed all patients given 1(st) salvage therapy for AML at M.D. Anderson Cancer Center from 1995–2004, focusing on patients given HSCT or chemotherapy without HSCT (a) as second salvage after 1(st) salvage failed to produce CR or (b) in 1(st) salvage-induced CR. Median survival in group (a) was 5.1 months for HSCT (n=84) vs. 2.3 months for chemotherapy (n=200, p=0.004) and, in group (b), was 11.7 months for HSCT (n=46) vs. 5.6 months for chemotherapy (n=66, p<0. 001). HSCT was associated with a survival benefit in each of 8 subgroups defined by age </≥50, high-risk cytogenetics or not, and treatment in 1(st) salvage-induced CR or 2(nd) salvage, and also in 5 of 6 subgroups defined by age </≥50 and 1st complete remission (CR1) duration (primary refractory, CR1 ≤36 weeks, CR1 >36 weeks). Our data suggest that HSCT is preferable to chemotherapy alone in these poor prognosis patients with particular benefit noted in patients <50.